Conjugated linoleic acid content in milk of Chilean Black Friesian cows under pasture conditions and supplemented with canola seed (Brassica napus) concentrate - Avilez Ruiz, J. P.; von Fabeck, G.; García-Gómez, F.; Alonzo, M.; Delgado Pertíñez, M. (Spanish Journal of Agricultural Research, 2013)
At present, there is limited and contradictory information about the effects of the use of canola (Brassica napus) seed as supplement on the contents of conjugated linoleic acid (CLA) in milk of grazing cows. The objective of this study was to evaluate the effect of a dietary supplement with canola seed on the production and composition of milk, and CLA concentration in Chilean Black Friesian cows under pasture conditions. Three experiments were done. Experiment 1: control group was fed 5 kg d-1 of commercial concentrate without canola (0-TC1) and treatment group that was fed 3.75 kg of commercial concentrate plus 1.16 kg of whole canola seed (1.16-TC1). Experiment 2: Control group was fed 8 kg d-1 commercial concentrate without canola (0-TC2) and treatment group that was fed 6.2 kg of commercial concentrate plus 1.2 kg of ground canola seed (1.2-TC2). Experiment 3: control group was fed 6 kg d-1 commercial concentrate without canola (0-TC3) and treatment group was fed 6 kg of commercial concentrate with 20% of whole canola seed (1.2 kg d-1, 1.2-TC3). The duration of each experiment was 60 days. No differences in milk production and quality were observed among the experimental groups in every assay. The CLA isomers trans-10, cis-12 and cis-10, cis-12 were higher than those normally found in the scientific literature. There was no effect of the inclusion of canola seed on total CLA content or the content of cis-9, trans-11, trans-10, cis-12 and cis-10, cis-12 isomers.